Radial glia phagocytose axonal debris from degenerating overextending axons in the developing olfactory bulb. Issue 2 (30th August 2014) - Amaya, Daniel A.; Wegner, Michael; Stolt, C. Claus; Chehrehasa, Fatemeh; Ekberg, Jenny A.K.; St John, James A.
ABSTRACT Axon targeting during the development of the olfactory system is not always accurate, and numerous axons overextend past the target layer into the deeper layers of the olfactory bulb. To date, the fate of the mis‐targeted axons has not been determined. We hypothesized that following overextension, the axons degenerate, and cells within the deeper layers of the olfactory bulb phagocytose the axonal debris. We utilized a line of transgenic mice that expresses ZsGreen fluorescent protein in primary olfactory axons. We found that overextending axons closely followed the filaments of radial glia present in the olfactory bulb during embryonic development. Following overextension into deeper layers of the olfactory bulb, axons degenerated and radial glia responded by phagocytosing the resulting debris. We used in vitro analysis to confirm that the radial glia had phagocytosed debris from olfactory axons. We also investigated whether the fate of overextending axons was altered when the development of the olfactory bulb was perturbed. In mice that lacked Sox10, a transcription factor essential for normal olfactory bulb development, we observed a disruption to the morphology and positioning of radial glia and an accumulation of olfactory axon debris within the bulb. Our results demonstrate that during early development of the olfactory system, radial glia play an important role in removing overextended axons from the deeper layers of the olfactory bulb. J. Comp. Neurol. 523:183–196, 2015. © 2014 Wiley Periodicals, Inc.